Patient-Centered Design of an Information Management Module for a Personally Controlled Health Record - Sox, Colin M; Gribbons, William M; Loring, Beth A; Mandl, Kenneth D; Batista, Rosanna; Porter, Stephen C (JMIR Publications, 2010)
BackgroundThe development of health information technologies should be informed by iterative experiments in which qualitative and quantitative methodologies provide a deeper understanding of the abilities, needs, and goals of the target audience for a personal health application. ObjectiveOur objective was to create an interface for parents of children with attention-deficit hyperactivity/disorder (ADHD) to enter disease-specific information to facilitate data entry with minimal task burden. MethodsWe developed an ADHD-specific personal health application to support data entry into a personally controlled health record (PCHR) using a three-step, iterative process: (1) a needs analysis by conducting focus groups with parents of children with ADHD and an heuristic evaluation of a prerelease version of a PCHR, (2) usability testing of an initial prototype personal health application following a "think aloud" protocol, (3) performance testing of a revised prototype, and (4) finalizing the design and functionality of the ADHD personal health application. Study populations for the three studies (focus groups and two usability testing studies) were recruited from organizations in the greater Boston area. Study eligibility included being an English- or Spanish-speaking parent who was the primary caretaker of a school-age child with ADHD. We determined subjects' health literacy using the Test of Functional Health Literacy in Adults (TOFHLA). We assessed subjects' task burden using the National Aeronautics and Space Administration (NASA) Task Load Index. To assess the impact of factors associated with the time spent entering data, we calculated Pearson correlation coefficients (r) between time on task and both task burden and subject characteristics. We conducted t tests to determine if time on task was associated with successful task completion. ResultsThe focus groups included three cohorts: 4 Spanish-speaking parents with diverse health literacy, 4 English-speaking parents with lower health literacy, and 7 English-speaking parents with higher health literacy. Both the initial usability testing cohort (n = 10) and the performance-testing cohort (n = 7) included parents of diverse health literacy and ethnicity. In performance testing, the prototype PCHRs captured patient-specific data with a mean time on task of 11.9 minutes (SD 6.5). Task burden experienced during data entry was not associated with successful task completion (P = .92). Subjects' past computer experience was highly correlated with time on task (r = .86, P = .01), but not with task burden (r = .18, P = .69). The ADHD personal health application was finalized in response to these results by (1) simplifying the visual environment, (2) including items to support users limited by health literacy or technology experience, and (3) populating the application's welcome screen with pictures of culturally diverse families to establish a personal family-oriented look and feel. ConclusionsOur patient-centered design process produced a usable ADHD-specific personal health application that minimizes the burden of data entry.